CaMKIIβ Regulates Oligodendrocyte Maturation and CNS Myelination - Waggener, Christopher T. (Society for Neuroscience, 2013)
CNS myelination and the maturation of the myelinating cells of the CNS, namely oligodendrocytes, are thought to be regulated by molecular mechanisms controlling the actin cytoskeleton. However, the exact nature of these mechanisms is currently only poorly understood. Here we assessed the role of calcium/calmodulin-dependent kinase type II (CaMKII), in particular CaMKIIβ, in oligodendrocyte maturation and CNS myelination. Using in vitro culture studies, our data demonstrate that CaMKIIβ is critical for the proper morphological maturation of differentiating oligodendrocytes, an aspect of oligodendrocyte maturation that is mediated to a large extent by changes in the cellular cytoskeleton. Furthermore, our data provide evidence for an actin-cytoskeleton-stabilizing role of CaMKIIβ in differentiating oligodendrocytes. Using Camk2b knock-out and Camk2b(A303R) mutant mice, our data revealed an in vivo functional role of CaMKIIβ in regulating myelin thickness that may be mediated by a non-kinase-catalytic activity. Our data point toward a critical role of CaMKIIβ in regulating oligodendrocyte maturation and CNS myelination via an actin-cytoskeleton-regulatory mechanism.